The Role of Superoxide Dismutase 1 in Amyotrophic Lateral Sclerosis: Identification of Signaling Pathways, Regulators, Molecular Interaction Networks, and Biological Functions through Bioinformatics - Sharad Kumar Suthar; Sang-Yoon Lee (Brain Sciences, 2023)
Mutations in superoxide dismutase 1 (SOD1) result in misfolding and aggregation of the protein, causing neurodegenerative amyotrophic lateral sclerosis (ALS). In recent years, several new SOD1 variants that trigger ALS have been identified, making it increasingly crucial to understand the SOD1 toxicity pathway in ALS. Here we used an integrated bioinformatics approach, including the Ingenuity Pathway Analysis (IPA) tool to analyze signaling pathways, regulators, functions, and network molecules of SOD1 with an emphasis on ALS. IPA toxicity analysis of SOD1 identified superoxide radicals’ degradation, apelin adipocyte, ALS, NRF2-mediated oxidative stress response, and sirtuin signaling as the key signaling pathways, while the toxicity of SOD1 is exerted via mitochondrial swelling and oxidative stress. IPA listed CNR1, APLN, BTG2, MAPK, DRAP1, NFE2L2, SNCA, and CG as the upstream regulators of SOD1. IPA further revealed that mutation in SOD1 results in hereditary disorders, including ALS. The exploration of the relationship between SOD1 and ALS using IPA unveiled SOD1-ALS pathway molecules. The gene ontology (GO) analysis of SOD1-ALS pathway molecules with ShinyGO reaffirmed that SOD1 toxicity results in ALS and neurodegeneration. The GO analysis further identified enriched biological processes, molecular functions, and cellular components for SOD1-ALS pathway molecules. The construction of a protein–protein interaction network of SOD1-ALS pathway molecules using STRING and further analysis of that network with Cytoscape identified ACTB followed by TP53, IL6, CASP3, SOD1, IL1B, APP, APOE, and VEGFA as the major network hubs. Taken together, our study provides insight into the molecular underpinning of SOD1’s toxicity in ALS.